Fluorescently Labeled Adenovirus with pIX-EGFP for Vector Detection - Long P. Le; Maaike Everts; Igor P. Dmitriev; Julia G. Davydova; Masato Yamamoto; David T. Curiel (Molecular Imaging)
Adenoviruses are extensively studied in terms of their use as gene therapy vectors and pathogenesis. These vectors have been targeted on both transcriptional and transductional levels to achieve cell-specific gene delivery. Current detection strategies, including reporter gene expression, viral component detection, and vector labeling with fluorophores, have been applied to analyze adenoviral vectors; however, these methods are inadequate for assessing transductional targeting. As an alternative to conventional vector detection techniques, we developed a specific genetic labeling system whereby an adenoviral vector incorporates a fusion between capsid protein IX and EGFP. DNA packaging and thermostability were marginally hampered by the modification while DNA replication, cytopathic effect, and CAR-dependent binding were not affected. The fluorescent label was associated with the virus capsid and conferred a fluorescent property useful in detecting adenoviral particles in flow cytometry, tracking, and tissue sections. We believe our genetic adenovirus labeling system has important implications for vector development, detecting adenovirus vectors in targeting schemes, and studying adenovirus biology. In addition, this technique has potential utility for dynamic monitoring of adenovirus replication and spread.